Unlicensed vehicle. Its contributions on the movements of the Cini's population / Azlan Ismail - Azlan, Ismail (Faculty of Business and Management, 1988)
Cini is a newly developed territory in Pahang. The project is developed by an agency called DARA. Before Cini was developed, it was covered by huge jungle. It has an area of 16195.92 hectare of land. Where 931.03 hectare is agricultural area and 305 hectare is mining area. Cini is divided into six (6) small scheme which are.Among these schemes, Felda Cini 1 and Felda Cini Timur are the centre for any activities. DARA has developed these two schemes into administrative centre in Cini, where facilities such as government office, shops and others can be found herea